2016
DOI: 10.1038/srep39027
|View full text |Cite
|
Sign up to set email alerts
|

The Management and Prognostic Prediction of Adenocarcinoma of Appendix

Abstract: Malignant tumours of the appendix are quite rare, especially appendiceal adenocarcinomas, which may be difficult to detect preoperatively or intraoperatively. We collected data for 1404 patients with adenocarcinoma of the appendix from the Surveillance, Epidemiology, and End Results Program (SEER) database to explore the potential associations between clinicopathological factors and overall survival. Furthermore, a novel nomogram for predicting prognosis was developed based on our analysis of the SEER data. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 22 publications
(31 reference statements)
0
24
1
2
Order By: Relevance
“…Recently, Asare et al demonstrated that systematic chemotherapy could lead to a significantly improved OS without considering the history feature of the adenocarcinoma (HR:0.79; 95% CI: 0.69-0.90; P = 0.0005 and HR:0.84; 95% CI: 0.75-0.95; P = 0.004 for mucinous and nonmucinous, respectively). Moreover, systemic chemotherapy seems to have no effects on the patients with mucinous and welldifferentiated adenocarcinomas [20,21]. In our study, multivariate analysis revealed that patients with CCR0/1/ 2 score had significantly improved 5-year overall survival rate than those with CCR3, whereas The OS times for the cohort based on CCR score of tumors were 28 months and 12 months, respectively, for CCR0/1/2, and CCR3.…”
Section: Discussionmentioning
confidence: 49%
“…Recently, Asare et al demonstrated that systematic chemotherapy could lead to a significantly improved OS without considering the history feature of the adenocarcinoma (HR:0.79; 95% CI: 0.69-0.90; P = 0.0005 and HR:0.84; 95% CI: 0.75-0.95; P = 0.004 for mucinous and nonmucinous, respectively). Moreover, systemic chemotherapy seems to have no effects on the patients with mucinous and welldifferentiated adenocarcinomas [20,21]. In our study, multivariate analysis revealed that patients with CCR0/1/ 2 score had significantly improved 5-year overall survival rate than those with CCR3, whereas The OS times for the cohort based on CCR score of tumors were 28 months and 12 months, respectively, for CCR0/1/2, and CCR3.…”
Section: Discussionmentioning
confidence: 49%
“…Despite better prognosis was observed in patients with well-differentiated adenocarcinomas of the appendix than those with poorly differentiated adenocarcinomas and the AJCC TNM system defined histological grade was considered as a critical prediction index for the prognosis in patients with appendiceal adenocarcinoma, distinctly different Cancer-specific survival was found in Stage IV (according toAJCC Staging Manual 7th edition) patients with moderately and poorly differentiated mucinous adenocarcinomas were found, which against the combination of these 2 histological grades according to recent publication [11]. In a previous study by Xie et al [12], they provided a better and more accurate prognosis prediction model in patients with appendiceal adenocarcinoma based on the data obtained from SEER database. More importantly, they also suggested that the depth of adenocarcinoma invasion may be employed as a predict index for surgical approach optimization.…”
Section: Discussionmentioning
confidence: 98%
“…histological grade and distant metastases), in patients who underwent surgical treatment, that were more accurate than those generated using the traditional AJCC TNM Staging system(23). However, due to the limitations of the SEER database, information regarding the administration of chemotherapy could not be obtained (23). Despite the novel ndings of this study, this is a retrospective study with its inherent limitations.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to clinico-pathological high-risk features high-quality prognostic biomarkers could also be useful clinically to estimate proper therapeutic strategies or to predict prognosis(23). A nomogram predict model proposed by Xie et al, who collected data for 1404 patients with adenocarcinoma of the appendix from the Surveillance, Epidemiology, and End Results Program (SEER) database, noted that different stages meant disparate therapies and discrepant prognosis between low-and high-risk patients, especially in stage I-III adenocarcinoma of the appendix(23). Their novel nomogram prognosis prediction model contained seven clinical factors (age, marital status, depth of tumor invasion, total number of resected regional lymph nodes, number of metastatic lymph nodes,…”
mentioning
confidence: 99%